(untitled) (Communicare: Journal for Communication Studies in Africa, 2022)
A group of Zimbabwean bloggers formed a voluntary association (the Zimbabwe Online ContentCreators-ZOCC) aimed at protecting the credibility of their online content against fake newsby producing factual content. Like the media elsewhere in the world, Zimbabwean media havebeen influenced by the phenomenon of “post-truth”, a term relating to the rise of an era in whichemotions rather than facts seem to sway public opinion, and where populism overshadows basicprinciples of reason and veracity. Qualitative interviews with members of this Association sought tounderstand the value of membership of this group in reducing the circulation of disinformation andmisleading content. Firstly, results show that to some extent the Association inculcated a sense ofidentity and belonging which bind members’ commitment to the group’s core values such as beingbalanced, independent, truthful, accurate and responsible. Mainstream media organisations,bloggers, vloggers and animators can use the power of their professional identity to coalesceas a buffer against fake news. However, this study noted that as the group is voluntary-based, itlacks authority and disciplinary power to enforce compliance with group norms, thereby runningthe risk that some members can violate the same values with impunity. Secondly, in Zimbabwe,there are strong relationships between the type of falsified and misleading news and the sociopoliticaland economic context. Information might be published for its “feel good” effect (at theexpense of its credibility and accuracy) in a context where democracy and economic prosperityare illusory to many.